Penyuluhan Pengukuran Berat Badan Dan Tinggi Badan Untuk Pengontrolan Obesitas Sebagai Faktor Pemicu Gout Arthritis - Elida Sinuraya; Idahwati; Arlan Pioner; Gloria Grace Indah Hia (Pelita Medika, 2022)
Background: There is a change in people's lifestyles where excessive energy intake and lack of physical activity make a person easy to be in a state of obesity. High fat levels will limit the expenditure of uric acid. The buildup of uric acid in the blood causes joint pain which is a symptom of gouty arthritis. This community service aims to provide education to the community for controlling obesity as a triggering factor for gout arthritis. Methods: The activity was carried out using a demonstration method of measuring weight and height and calculating BMI to detect obesity. Results: The results of this activity showed that 100% of the community was able to demonstrate the measurement of weight and height and 93% were able to calculate BMI correctly to detect obesity. Conclusion: Counseling on measuring height and weight has increased the ability of Sari Mutiara Indonesia University students to control obesity as a triggering factor for gout arthritis.